Bartter Syndrome Type 1 Due to Novel SLC12A1 Mutations Associated With Pseudohypoparathyroidism Type II. Issue 2 (24th February 2023) - Kiuchi, Zentaro; Nozu, Kandai; Yan, Kunimasa; Jüppner, Harald
Abstract: Bartter syndrome type 1 is caused by mutations in the solute carrier family 12 member 1 ( SLC12A1 ), encoding the sodium-potassium-chloride cotransporter-2 (NKCC2). In addition to causing renal salt-losing tubulopathy, SLC12A1 mutations are known to cause nephrocalcinosis due to hypercalciuria, as well as failure to thrive associated with abnormal calcium and phosphorus homeostasis. We report a now 7-year-old Japanese girl with polyuria, hyponatremia, hypokalemia, and metabolic alkalosis, in whom compound heterozygous novel SLC12A1 mutations were identified. Elevated parathyroid hormone (PTH) levels were consistently noted after the age of 1 year in conjunction with gradually declining serum calcium and increasing serum phosphorus levels. To confirm suspected PTH-resistance, Ellsworth Howard tests were performed at the ages of 6 years 8 months and 6 years 10 months in the absence or presence of ibuprofen, respectively. Urinary adenosine 3′, 5′-cyclic monophosphate excretion increased on both occasions in response to PTH(1-34) infusion suggesting pseudohypoparathyroidism type II. However, only during treatment with ibuprofen did PTH induce an almost normal phosphaturic response. The nonsteroidal anti-inflammatory drugs thus enhanced growth velocity, alleviated hypercalciuria, and increased PTH-stimulated urinary phosphorus excretion without significantly affecting renal function.